1987
DOI: 10.1620/tjem.153.395
|View full text |Cite
|
Sign up to set email alerts
|

A continuous sampling model of the seminal vesicle fluid in rat.

Abstract: A continuous sampling model of the fluid excreted from the unilateral seminal vesicle was devised in the rat. Each 12 hr change in the volume was measured in 14 sexually mature male rats by use of tubing. If we assume the excretion of a small volume (less than 4 pl) as the resting level, 3 of 14 rats showed only the resting level. The excretion of a large volume was sometimes observed in the 11 other rats both in daytime and nighttime. This model would be promising for investigations of the seminal vesicles fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1989
1989
1992
1992

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…On the other hand, our previous study, using an original method to measure the fluid volume excreted from the rat seminal vesicle in an unanesthetized condition, revealed that the seminal vesicle fluid was sometimes excreted in large volume (69.2,ul maximally) in addition to the resting level of less than 4 pl for 12 hr (Terasaki et al 1987). The seminal vesicle fluid was, therefore, considered to be excreted gradually or episodically in volume.…”
Section: Discussionmentioning
confidence: 90%
“…On the other hand, our previous study, using an original method to measure the fluid volume excreted from the rat seminal vesicle in an unanesthetized condition, revealed that the seminal vesicle fluid was sometimes excreted in large volume (69.2,ul maximally) in addition to the resting level of less than 4 pl for 12 hr (Terasaki et al 1987). The seminal vesicle fluid was, therefore, considered to be excreted gradually or episodically in volume.…”
Section: Discussionmentioning
confidence: 90%